Taxonomic reassessment of Viola aetolica and Viola elegantula (V. sect. Melanium, Violaceae), with descriptions of two new species from the Balkan Peninsula - Tomović, Gordana; Niketić, Marjan; Lazarević, Maja; Melovski, Ljupčo (Phytotaxa, 2016)
On the basis of morphometric and karyological analysis, a new taxonomic treatment of the endemic orophytes Viola aetolica and V. elegantula is presented and two new species, V. pseudaetolica and V. kopaonikensis from the central part of the Balkan Peninsula, are described. The Balkan endemic V. pseudaetolica differs from the similar Southern Balkan endemic V. aetolica by its rather large bright yellow flowers, conspicuously denticulate and pubescent sepals and longer spur; it also shares some features with V. elegantula and V. kopaonikensis. V. kopaonikensis is a Serbian endemic plant, morphologically well separated from the closest Balkan endemic species V. elegantula by denser indumentum, relatively longer middle leaves, smaller and strictly yellow petals and relatively shorter spur. The differences among these four species are particularly pronounced when considering the ratios between petals and sepals, petals length/width and spurs length/width. Ecology, distribution and nomenclature of these two new species are also presented and discussed.